Analisis Determinan Harga Saham Perusahaan Sektor Consumer Goods di Bursa Efek Indonesia (BEI) - Natasha Maulida Aulia (2021)
The purpose of this quantitative research is to understand whether profitability (ROE), leverage (DER), and inflation give significant impact to stock price of consumer goods companies listed at Indonesia Stock Exchange (IDX). This research will analyze 56 consumer goods companies listed at IDX for the period of 2017 to 2019. The sample used is purposive sampling method and obtained through samples on 32 consumer goods companies. The hypothesis and data analysis are using data panel regression analysis supported by E-Views 10 and Microsoft Excel 2013 with 95% level of confidence. The result of this research will prove that profitability (ROE) positively impacted to stock price, while leverage (DER) brings negative impact, and inflation has no impact to the price.